2003
DOI: 10.1051/0004-6361:20030235
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotron spectroscopy of HU Aquarii

Abstract: Abstract. We present the results of a combined analysis of low-resolution spectroscopy and high-speed optical photometry of the bright eclipsing polar HU Aqr, obtained in its high accretion state. Cyclotron harmonic emission in a field of B 34 MG became evident and could be traced through the whole optical bright phase. The cyclotron harmonics display an asymmetric motion as a function of phase which requires a certain forward tilt of the magnetic field lines in the emission region. The optical bright phase is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 11 publications
6
21
1
Order By: Relevance
“…This is opposite to what is observed in other polars where the highest redshift was observed when the accretion spot was approaching the limb of the WD (see e.g. Schwope et al 2003;Burwitz et al 1996, for the cases of HU Aqr and RX J0453.4−4213), and it is contrary to what is expected for plasma emission from a point-like, isothermal accretion region. As a result, this observation could be evidence of an extended cyclotron-emitting region with successively self-eclipsing parts belonging to regions of slightly different field strengths.…”
Section: Optical Spectroscopycontrasting
confidence: 62%
See 1 more Smart Citation
“…This is opposite to what is observed in other polars where the highest redshift was observed when the accretion spot was approaching the limb of the WD (see e.g. Schwope et al 2003;Burwitz et al 1996, for the cases of HU Aqr and RX J0453.4−4213), and it is contrary to what is expected for plasma emission from a point-like, isothermal accretion region. As a result, this observation could be evidence of an extended cyclotron-emitting region with successively self-eclipsing parts belonging to regions of slightly different field strengths.…”
Section: Optical Spectroscopycontrasting
confidence: 62%
“…10) using the models in a series of papers (see e.g. Campbell et al 2008;Schwope et al 2003, and references therein).…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…been slow. Early follow-up observations after the identification with the HEAO1 scanning modulation collimator experiment (Remillard et al 1986) revealed properties common to the class of AM Herculis binaries: variations at optical and X-ray wavelengths with a tentative spin period of 200 min, strong circular polarisation (mostly of positive sign), optical low states down to V ≥ 17 m as measured from Harvard plates and the detection of cyclotron humps consistent with a magnetic field strength of 40.8 MG (Cropper et al 1989) or 28 MG (Schwope 1991).…”
Section: Introductionmentioning
confidence: 97%
“…Data of highest resolution and sufficient signal-to-noise can resolve the Roche lobe in Doppler coordinates (Schwarz et al 2002) and reveal asymmetric illumination of the secondary (Schwope et al 1997;Watson et al 2003). (b) Emission from the stream leaving the secondary star through the L 1 -point, seen as a cometary tail parallel to the v x axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation